Talleres “sobre los juegos recreativos para el mejoramiento de la motricidad fina y gruesa de los estudiantes del quinto año de educación básica, para disminuir el estrés escolar y mejorar el proceso de enseñanza aprendizaje en los niños de la escuela “Luis Fernando Vivero” de la parroquia Juan Montalvo, cantón Latacunga, provincia Cotopaxi, durante el año lectivo 2014/2015 - Almache Pincay, Karla Ibeth (2015)
The theme of recreational games is important for who make up the educational unit, thinking in the benefit that this research will involve in the search for new changes to the institution and whether the development of society. In that perspective, they have been promoting and implementing projects and activities that contribute to intellectual improvement, motor and psychic in the children. A part of the whole of the entire educational community that we must give more importance to try this issue are the children who need the most attention, both by teachers, parents and those we are the working on the thesis topic….